First question.
We must subtitute w=-13 into the given equation:
![(-5(-13)-6)-(-4(-13)+7)=14](https://img.qammunity.org/2023/formulas/mathematics/college/n51fw1njgku5t8mtqntc1lpviwb0w1d6j5.png)
then, we have
![\begin{gathered} (65-6)-(52+7)=14 \\ 59-59=14 \\ 0=14\text{ its an absurd !!} \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/k75ourvrpcwh6lfxhk9opj2u1xna4ms3bk.png)
so, the answer is false.
Second question.
We must substitute c=-3 into the given equation:
![-(-3)-3=-2(-3)-6](https://img.qammunity.org/2023/formulas/mathematics/college/zr6koxbk3pfvey9vsmwnukabgm2qfghgrg.png)
which gives
![\begin{gathered} 3-3=6-6 \\ 0=0\text{ thats correct !!} \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/8l8d23jbdpsryuaxth7mr4rkuu8azmz658.png)
so, the answer is true.
Third question.
We must substitute z=12 into the given equation:
![4(6(12)+7)=2(5(12)+98)](https://img.qammunity.org/2023/formulas/mathematics/college/3edgfgq9gs1wvgdxgj9exfvfi40ooj4e3d.png)
which gives
![\begin{gathered} 4(72+7)=2(60+98) \\ 4(79)=2(158) \\ 316=316\text{ thats correct!!} \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/ttv47uv5ed19ukbxhpbaf8juc7fkut8n1k.png)
so, the answer is true.
Fourth question.
We must substitute y=-5 into the given equation:
![3(-5)+2=4(-5)+7](https://img.qammunity.org/2023/formulas/mathematics/college/xx2zb0qirmrknefw91lw26ui7hbonjmjng.png)
which gives
![\begin{gathered} -15+2=-20+7 \\ -13=-13\text{ thats correct !!} \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/l0p05fj91sgl30w69hm3y1crtwsgfzzvyg.png)
so, the answer is true.